2014
DOI: 10.1007/s11999-014-3809-1
|View full text |Cite
|
Sign up to set email alerts
|

Is Curettage and High-speed Burring Sufficient Treatment for Aneurysmal Bone Cysts?

Abstract: Level IV, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 4 publications
1
51
0
Order By: Relevance
“…In straightforward cases that do not risk the physis and are relatively easy to access from an anatomic standpoint, intralesional curettage may be preferable in providing definitive treatment of ABC. 46,47 The results of this study support both the effect of doxycycline to target ABC tumor reduction and bony healing. In addition to the recognized effects of doxycycline on giant cell function/apoptosis, MMP inhibition, and VEGF inhibition, our experience supports a primary effect of doxycycline on ABC stromal resulting in necrosis, 39 translating into reduced ABC tumor volume with healing as measured radiographically (P < 0.001).…”
Section: Discussionsupporting
confidence: 68%
“…In straightforward cases that do not risk the physis and are relatively easy to access from an anatomic standpoint, intralesional curettage may be preferable in providing definitive treatment of ABC. 46,47 The results of this study support both the effect of doxycycline to target ABC tumor reduction and bony healing. In addition to the recognized effects of doxycycline on giant cell function/apoptosis, MMP inhibition, and VEGF inhibition, our experience supports a primary effect of doxycycline on ABC stromal resulting in necrosis, 39 translating into reduced ABC tumor volume with healing as measured radiographically (P < 0.001).…”
Section: Discussionsupporting
confidence: 68%
“…Keçeci et al 21 did not report any significant difference in terms of local recurrence between patients treated with curettage and bone grafting without adjuvants and patients treated with curettage and bone grafting beside burring or phenol usage. On the other hand, using curettage, burring, and bone grafting resulted in lower recurrence rates 15, 22. Also adding electrocautery and phenol in addition to burring have been suggested by the others 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, Steffner et al reported a 12.5 % postoperative fracture rate with argon beam compared to none in the curettage and burr group, which is postulated as stemming from the argon beam resulting in desiccation and osteonecrosis [35]. The widespread adoption of argon beam coagulation has been stifled as argon beam technology may not be part of the armamentarium of many operating rooms and surgeons may be unfamiliar with the technique [36].…”
Section: Argon Beam Coagulationmentioning
confidence: 99%